Prevalence of exercise-induced arterial hypoxemia in distance runners at sea level - Constantini, K.; Tanner, D. A.; Gavin, T. P.; Harms, C. A.; Stager, J. M.; Chapman, R. F. (Medicine & Science in Sports & Exercise, 2017)
PURPOSE: It has been reported that ~50% of endurance-trained men demonstrate exercise-induced arterial hypoxemia (EIAH) during heavy exercise. However, this often-cited prevalence rate comes from a single study using a cohort of 25 highly trained men who completed maximal cycle ergometry. As arterial oxyhemoglobin saturation (SpO2) during maximal exercise is reported to be significantly lower during treadmill versus cycle ergometry in the same subjects, we hypothesized that the prevalence of EIAH would be greater than previously reported (and commonly referenced) in a larger cohort of highly endurance-trained men during maximal treadmill running.